Foreign Language Classroom Anxiety Scale (FLCAS) Analysis of Students Speaking Anxiety in EFL Classroom - Firda Yuliawati (Program Studi Pendidikan Bahasa Inggris, Fakultas Keguruan dan Ilmu Pendidikan, Universitas Muhammadiyah Cirebon, 2019)
This research aims at identifying the factors of students’ speaking anxiety and explaining the students’ strategies in overcoming their anxiety of speaking English in the classroom. Universitas Muhammadiyah Cirebon is chosen as the site for this research. There were 28 students who participated in this research. The data were collected using Foreign Language Classroom Anxiety Scale (designed by Horwitz et al., 1986) and interview. The research found that there are 56% of the students experienced the test anxiety, 58% of the students feel anxious in communicative apprehension, and 59% of the students were getting anxious in fear of negative evaluation. The factors of students’ anxiety in speaking English is categorized into three type three major type of anxiety, namely test anxiety, communicative apprehension and fear of negative evaluation. This research also identifies three strategies used by the students to overcome their anxiety in speaking: Preparation, relaxation and expressive reaction. Keywords: Speaking Anxiety; Foreign Language Classroom Anxiety Scale (FLCAS).